2022
DOI: 10.3390/membranes12100987
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Castor Oil-Based Ion Selective Electrode (ISE) with Active Agent 1,10-Phenanthroline for Aqueous Pb2+ Analysis

Abstract: This research has successfully fabricated ion selective electrode (ISE) for Pb2+ using castor oil (Ricinus communis L.)-based polyurethane (PU) membrane with 1,10‒phenanthroline as the active agent. The sensitivity of the Pb2+ ISE obtained is 27.25 mV/decade with a linear range of [Pb(NO3)2] of 10−10–10−5 M and a coefficient of determination (R2) of 0.959. The system response reaches stability after 25 s of measurement. The Pb2+ has a detection limit of 10−10 M and gives a stable response at pH 7–8 with a 15-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The dope solution was prepared using 3.5 grams of commercial castor oil of the Ricinus communis L. mixed with 10 mg of 1,10-phenanthroline in a 50 mL Beaker glass and stirred for 3 hours until homogeneous solution obtained and then reacted with 1.75 grams of TDI followed by heating for 15 minutes at 60 o C. The solution obtained is a clear yellowish dope solution. The same results have also been reported by [11].…”
Section: Dope Membrane Solution Preparationsupporting
confidence: 89%
“…The dope solution was prepared using 3.5 grams of commercial castor oil of the Ricinus communis L. mixed with 10 mg of 1,10-phenanthroline in a 50 mL Beaker glass and stirred for 3 hours until homogeneous solution obtained and then reacted with 1.75 grams of TDI followed by heating for 15 minutes at 60 o C. The solution obtained is a clear yellowish dope solution. The same results have also been reported by [11].…”
Section: Dope Membrane Solution Preparationsupporting
confidence: 89%
“…Moreover, several studies have shown the use of ISE on the determination of total fluorine on different matrices, such as foams, fuels, lubricants, and organic materials [ 12 , 13 , 14 ]. Additionally, the successful fabrication of ISE from a polyurethane membrane for lead analysis was reported in several research studies [ 15 , 16 , 17 ]. An overview of common analytical techniques for the evaluation of TF/TOF and PFAS [ 18 ] is described in Table 1 .…”
Section: Introductionmentioning
confidence: 99%